The Relationship between Prediabetes and Prehypertension with Vascular Elasticity in Medical Students - Kia Iglesias Pangaribuan; Nurfitri Bustamam; Aulia Chairani; Marlina Dewiastuti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Prediabetes and prehypertension are known to affect vascular elasticity, and the prevalence of these conditions among young adults is increasing. This study examines the relationship between prediabetes and prehypertension with vascular elasticity in medical students. The study utilized a cross-sectional design and the technique of simple random sampling, involving a total of 69 students. The research subjects' criteria were medical students aged 18–25 years who were non-smokers, did not consume alcohol, had no history of diabetes or hypertension, and were not taking medications affecting blood pressure or blood glucose levels. Vascular elasticity, blood pressure, and fasting blood glucose levels were measured using an Accelerated Photoplethysmograph Analyzer SA-3000P, a digital sphygmomanometer, and a glucometer, respectively. The findings indicated no differences in gender, BMI, age, and physical activity between the suboptimal vascular elasticity and the normal+optimal elasticity groups (p > 0.05). The Chi-square test identified significant differences in vascular elasticity between the prediabetes and normal groups (p = 0.009; PR = 1.6; CI = 1.1–2.2), the prehypertension and normal groups (p = 0.026; PR = 1.5; CI = 1.1–2.2), and the prediabetes+prehypertension and normal groups (p = 0.002; PR = 3.5; CI = 1.4–8.3). These findings indicate that prediabetes, prehypertension, or both conditions are associated with reduced vascular elasticity.